2020
DOI: 10.1016/j.eclinm.2020.100312
|View full text |Cite
|
Sign up to set email alerts
|

Estimating cancer incidence based on claims data from medical insurance systems in two areas lacking cancer registries in China

Abstract: Background: We aimed to establish a Medical-Insurance-System-based Cancer Surveillance System (MIS-CASS) in China and evaluate the completeness and timeliness of this system through reporting cancer incidence rates using claims data in two regions in northern and southern China. Methods: We extracted claims data from medical insurance systems in Hua County of Henan Province, and Shantou City in Guangdong Province in China from Jan 1, 2012 to Jun 30, 2019. These two regions have been considered to be high risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 18 publications
2
54
0
Order By: Relevance
“…This study also has several limitations. First, the basic medical insurance database lacks some detailed information, such as tumour stage, clinical characteristics, results of pathological examination and laboratory results, which limits the possibility to stratify the diagnosis in greater detail and analyze the data in more depth, similar to other previous studies based on claim data 58 , 59 . Second, rural inhabitants and certain urban populations, such as military soldiers are not included in the UEBMI and URBMI system because they have different types of medical insurance.…”
Section: Discussionmentioning
confidence: 99%
“…This study also has several limitations. First, the basic medical insurance database lacks some detailed information, such as tumour stage, clinical characteristics, results of pathological examination and laboratory results, which limits the possibility to stratify the diagnosis in greater detail and analyze the data in more depth, similar to other previous studies based on claim data 58 , 59 . Second, rural inhabitants and certain urban populations, such as military soldiers are not included in the UEBMI and URBMI system because they have different types of medical insurance.…”
Section: Discussionmentioning
confidence: 99%
“…First, information regarding the clinical treatment regimen of the participants was collected with linkage to claims data from the New Rural Cooperative Medical Scheme (NCMS), which is a government-run health insurance program in rural China with coverage of nearly 100% in the study area that had previously proved to be a reliable data source regarding cancer diagnosis and treatment. [13] , [14] , [15] Detailed claims records from the NCMS for all participants from January 2012 to September 2017 were carefully reviewed to confirm whether they had received cancer-related therapy, which included endoscopic therapy, radical surgery, radiotherapy, and chemotherapy.…”
Section: Methodsmentioning
confidence: 99%
“…Hua County is a predominantly rural area in northern Henan Province in China, which has 1¢07 million permanent residents and had a per capita Gross Domestic Product of 24,585 Yuan (US $3715) in 2018 [18À20]. The New Rural Co-operative Medical Care Scheme (NCMS) is the sole medical insurance system for rural residents, and this system has had coverage of 99% since 2010 [15]. The incidence rate of oesophageal cancer ranked second among cancer types in Hua County in 2018, and this rate was 2¢1 times as high as the national level [15,21].…”
Section: Study Sitementioning
confidence: 99%
“…In China, basic medical insurance systems are administered and operated by the government, and cover over 95% of the national population. In a previous study, we established the Medical-Insurance-System-based Cancer Surveillance System (MIS-CASS) and demonstrated that this approach is capable of complete and accurate identification of incident cancer cases, and allows reporting cancer incidence in a timely manner in two regions (six million residents altogether) which are not covered by PBCRs in China [15].…”
Section: Introductionmentioning
confidence: 99%